Failure analysis of three rigid block assemblies – A real collapse resulting in death. (March 2023) - Frappa, Giada; Pauletta, Margherita; Russo, Gaetano
Highlights: A practical method for the failure analysis of three rigid block assemblies is given. The overturning stability of a holy water stoup with pillar is analyzed. All possible collapse mechanisms of the three rigid block assembly are considered. Different inclinations of the external load applied to the stoup are considered. Preventive actions against disarticulation of rigid block assemblies are proposed. Abstract: The failure analysis of three rigid block assemblies is often necessary to assess the stability of architectural and historical assets. An analytical method for the assessment of the overturning stability of assemblies composed by three rigid blocks fitted atop one on another is proposed. The method takes account of several load configurations and all possible collapse mechanisms involving the overturning of one, two or three blocks. In the category of historical assets fall many holy water stoups with pillar, often realized as three rigid block assemblies. A great number of holy water stoups disarticulations occurred in Italy in the last decades, leading, in some cases, to children death. A 7 years old girl died due to the disarticulation of an historical holy water stoup in the Santa Chiara Church, in Udine, Italy, caused by the force applied by the girl on the basin. The stoup is realized as a three rigid block assembly with connections of the type mortise and tenon both between the basement and the shaft and between the shaft and the basin. In the connections the presence of mortar is detected. In order to evaluate the ability of the mortar to stabilize the connections between the three rigid blocks, the mineralogical and petrographic analyses of a mortar sample are performed. Moreover, a loading test is carried out in laboratory to obtain an experimental value of the holy water stoup failure load. This value is determined by applying a vertical force to the outer circumference of the basin. Then, in order to determine the holy water stoup failure load under an inclined force statically applied at the top of the basin, the stoup overturning stability is theoretically analysed. The analysis is performed considering all possible collapse mechanisms of the three rigid block assembly and the variability of the force inclination with respect to the horizontal plane. The performed analysis is suitable because it confirms that the disarticulation of the holy water stoup can be caused by a force applied by the kid at the top of the basin. The presented paper is the first one that analyses the overturning stability of three rigid block assemblies under external forces which do not depend on the single blocks masses and with variable direction.